Study of Densification Process and Microstructure for Highly Dense Doped MgB2 Bulk Samples - Yonamine, A. H. [UNESP]; Saeki, M. J. [UNESP]; Eiras, J. A.; dos Santos, D. I. [UNESP] (Springer, 2012)
In order to give a contribution in the subject of MgB2 processing technique to obtain low cost high density bulk samples with improved superconducting properties, studies on dilatometry and on the microstructures of in situ and ex situ MgB2 bulk samples prepared in the presence of carbon compounds are presented in this paper. The ex situ densification was performed by isostatic pressure followed by high temperature treatment in air, which promoted high density samples compared to the common magnesium diboride in situ samples. It was observed that each carbon compound addition (hydrocarbon-C8H18, SiC and silicon oil-SiC2H6O), corresponds to one microstructure, which can be noticed even after the ex situ process for sintering the pellets. Among the compounds, the SiC showed to present the most irregular structure for the in situ samples. However, this microstructure showed to change completely and reaches higher density (90 %) very rapidly when heat treated in the ex situ process. The X ray diffraction (XRD) analyses also revealed that the presence of spurious phases-like Mg2Si, Mg3B2O6, MgO and others-for the ex situ samples treated in air at high temperature.
Keywords: MgB2 microstructure; MgB2 processing; MgB2 carbon compounds doping; MgB2 ex situ processing; Dilatometry study on MgB2